KONSEP PENGELOLAAN EKOSISTEM PESISIR ( STUDI KASUS KECAMATAN ULUJAMI, KABUPATEN PEMALANG, JAWA TENGAH ) - Saraswati, Adinda Arimbi (Jurnal Teknologi Lingkungan, 2004)
As the coastal zone, Kabupaten Pemalang has an important strategic role for the fishery development at Java Island. Pemalang’s coastal zone is a bore of several rivers (estuary area) and this zone is a fertile maritime province so it’s potential to develop a dyke plantation. Meanwhile as Kabupaten Pemalang’s coastal zone have mangrove around, it’s require having conservation at this area and this situation may have a conflict of interest to developing a dyke plantation.Many of concept to deploy coastal zone to integrate on behalf of ecology and economic has been developed and implemented at Kabupaten Pemalang, so this coastal zone is become a useful zone and this area was developed with a good environmental.The difficulties of how to manage this area was how to deploy with varietymultifunction and this situation constantly have a conflict of interest especially how to developed a dyke plantation for economic against conservation. This chapter is to dwell on concepts which has been developed and implemented at Kabupaten Pemalang which cover the Mangrove Conservation, Silvofishery and Tumpangsari Programme.